Male breast cancer, clinical presentation, diagnosis and treatment: Twenty years of experience in our Breast Unit. (2016) - Sanguinetti, A.; Polistena, A.; Lucchini, R.; Monacelli, M.; Galasse, S.; Avenia, S.; Triola, R.; Bugiantella, W.; Cirocchi, R.; Rondelli, F.; Avenia, N.
Highlights: Male breast cancer (MBC) is a rare disease representing less than 1% of all malignancies in men andonly 1% of all incident breast cancers. Management consisted especially of radical mastectomy; followed by adjuvant radiotherapy and hormonal therapy with or without chemotherapy. Future research for better understanding of this disease at national or international level are needed to improve the management and prognosis of male patients. Abstract: Background: The male breast cancer (MBC) is a rare and represents less than 1% of all malignancies in men and only 1% of all breast cancers incident. We illustrate the experience of our team about the clinico-pathological characteristics, treatment and prognostic factors of patients treated over a period of twenty years . Results: Forty-seven patients were collected 1995–2014 at the Breast Unit of the Hospital of Terni, Italy. The average age was 67 years and the median time to diagnosis from the onset of symptoms was 16 months. The main clinical complaint was sub areolar swelling in 36, 76% of cases. Most patients have come to our attention with advanced disease. The histology of about ninety percent of the tumors were invasive ductal carcinoma. Management consisted mainly of radical mastectomy; followed by adjuvant radiotherapy and hormonal therapy with or without chemotherapy. The median follow-up was 38 months. The evolution has been characterized by local recurrences; in eight cases (17% of all patients). Metastasis occurred in 15 cases (32% of all patients). The site of bone metastases was in eight cases; lung in four cases; liver in three cases; liver and skin in one case and pleura and skin in one case. Conclusion: The male breast cancer has many similarities to breast cancer in women, but there are distinct functions that need to be appreciated. Future research for a better understanding of the disease should provide a better account of genetic and epigenetic characteristics of these forms; but, above all, epidemiological and biological cohorts numerically more consistent.